THE ROLE OF WORK-LIFE BALANCE AND EMPLOYEE LOYALTY ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF EMPLOYEES OF THE IMPLEMENTING CENTER FOR HOUSING AND SETTLEMENT AREA PROVISION IN NUSA TENGGARA I - Muhammad Firza Bachtiar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to analyze the influence of Work-Life Balance and Employee Loyalty on Organizational Citizenship Behavior (OCB) among employees of the Housing and Settlement Area Provision Implementation Center of Nusa Tenggara I. Organizational Citizenship Behavior (OCB) is voluntary employee behavior outside of formal duties that is beneficial to the organization. This study uses a quantitative approach with a population of 68 employees, using a saturated sampling technique. Data collection was carried out through a questionnaire using a Likert scale, and analyzed using multiple linear regression. The results of the study indicate that partially Work-Life Balance and Employee Loyalty have a positive and significant effect on OCB. Simultaneously, both variables also have a significant effect on OCB. This finding emphasizes the importance of government HR management paying attention to employee work-life balance and building employee loyalty.